The Good, the Bad and the Ugly: Risk, Uncertainty and Decision-Making by Victorian Fishers - Peter D. Dwyer; Monica Minnegal (Journal of Political Ecology, 2006)
In this paper, decision-making by Australian commercial fishers is explored with reference to aspects of risk or uncertainty that characterize their experience of the physical and biological environment, the socioeconomic environment and the environment of management. In these environments decisions are grounded in, respectively and particularly, skill, strategy and (often) recklessness. In a broader frame it is argued that ways in which fishers ‘place’ themselves in these distinct environments with respect to certainty, social identity, personhood, agency and temporal orientation have parallels with conventional anthropological and sociological representations of ‘premodern’, ‘modern’ and ‘late modern’ societies respectively. Our argument directs attention to the multidimensional life-worlds of fishers and serves as an ethnographically-based critique of the universalizing and essentializing themes of some recent approaches in social theory.